International law of state responsibility : an introduction - Kolb, Robert (Cheltenham, UK : Edward Elgar Publishing, 2017)
"Covering the key aspects of the topic [of public international law], [this book] combines an ... overview with use of specific case studies in order to provide a deeper understanding. The ... chapters are organized into two parts. Part one provides a structural overview of the law, with up-to-date coverage of practice and case law reflecting the key international law reports. Part two offers specific case studies, asking probing questions in order to explore how the international legal order deals with breaches of its norms and what rights and faculties are accorded to the aggrieved state."--
1. Concept and history -- 2. Internationally wrongful act -- 3. Attribution -- 4. Circumstances precluding wrongfulness -- 5. Legal effects of responsibility -- 6. Issues of collective and ancillary responsibility -- 7. Conclusion.
Includes bibliographical references (page 234) and index.
Keywords: Government liability (International law); International law: general; 86.50 constitutional law: general; Government liability (International law); State responsibility; Internationally wrongful acts; Accountability; Public international law